ISLAMIC PERSPECTIVE ON MARITAL RAPE - Susila, Muhammad Endriyo (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2013)
Marital rape has become a controversial issue in many countries including Indonesia. For the majority of the Indonesian people, it is impossible for rape to take place inside the marriage institution, however some other peoples believe that it possibly occurs. Since it is considered as a kind of rape anyway, those who agree with that concept, insist on the government of Indonesia to qualify marital rape as an offence. This is sounded usually by the human rights activists, especially the feminists. This research is aimed to elaborate the legal position of what so-call marital rape in Islam. As a country whose population is majority Muslim, it can be understood that the development of the Indonesian law is influenced by the Islamic values. This research provide an important reference to deal with the issue of the criminalization of marital rape in Indonesia.Since the research focuses more on the study of legal materials from various sources, it is qualified as a normative legal research. To support the collection of data, interview upon the competent legal experts has also been exercised. The standard of qualification of the legal experts involving in the interview are those who are interested in Islamic Law, especially Islamic Family law as well as Islamic Criminal Law.Â Â Â Based on the research finding, it is found that the type of the relationship between husband and wife as suggested in Islamic teaching naturaly prevents the what so-call marital rape to occur. It is difficult to imagine the existence of marital rape inside the Muslim familes, since the husband is bound with the obligation to treat her wife well (muâasyarah bil maâruf). In sexual matter, the doctrine of muâasyarah bil maâruf can be applied by respecting the need and the willingness of the wife in sexual matter. Meaning to say, the husband is obliged to fulfill his wife sexual desire in one side, and in the other side he is not allowed to force her wife for sex when she is unwilling. It is better for the husband to sacrifice him self (to be patient) rather than sacrificing his wife. A good husband must be wise in choosing the better choice relating to the above issue. A good husband must be patient (shabr) for not saying that who is not patient is not a good husband.Keywords: Marriage, Rape, and Marital Rape